2022
DOI: 10.3389/fped.2022.1051079
|View full text |Cite
|
Sign up to set email alerts
|

Can bacterial lysates be useful in prevention of viral respiratory infections in childhood? The results of experimental OM-85 studies

Abstract: Respiratory tract infections (RTI) are mainly viral in origin and among the leading cause of childhood morbidity globally. Associated wheezing illness and asthma are still a clear unmet medical need. Despite the continuous progress in understanding the processes involved in their pathogenesis, preventive measures and treatments failed to demonstrate any significant disease-modifying effect. However, in the last decades it was understood that early-life exposure to microbes, may reduce the risk of infectious an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In contrast, in a study of trained immunity also employing intranasal immunizations, protection against subsequent infection was induced by several Gram-negative bacterial species, but not by S. aureus or S. pneumoniae [41]. Of note, the immunomodulant compound OM-85 is a bacterial lysate mix containing lyophilized fragments of 21 common bacterial pathogens, including GAS, S. aureus and S. pneumoniae , and is used clinically to treat children suffering from recurrent lower respiratory tract infections [42, 43]. The exact mechanism(s) of action of this treatment regimen has not yet been elucidated, but as protection is evident also for viral pathogens, the mechanism of protection is believed to at least partially be attributed to induced trained immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study of trained immunity also employing intranasal immunizations, protection against subsequent infection was induced by several Gram-negative bacterial species, but not by S. aureus or S. pneumoniae [41]. Of note, the immunomodulant compound OM-85 is a bacterial lysate mix containing lyophilized fragments of 21 common bacterial pathogens, including GAS, S. aureus and S. pneumoniae , and is used clinically to treat children suffering from recurrent lower respiratory tract infections [42, 43]. The exact mechanism(s) of action of this treatment regimen has not yet been elucidated, but as protection is evident also for viral pathogens, the mechanism of protection is believed to at least partially be attributed to induced trained immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulation offers the best chance of reducing the development of asthma and asthma exacerbations in the future. Many small trials have shown efficacy, and immunomodulation is known to enhance Th1 immunity and interferon production 15 . Although these studies have not been sufficient to persuade authorities to promote its widespread introduction, they have been impressive enough to generate support for several large, randomized, double‐blind, placebo‐controlled, immunomodulation clinical trials that are now nearing completion.…”
Section: Figurementioning
confidence: 99%
“…Orally administered bacterial lysates of mixed respiratory pathogenic bacteria have been used for decades to prevent RTIs [ 174 ] in children [ 175 , 176 ] and in vulnerable adults [ 177 179 ]. Infection incidence, duration and severity were studied in randomised clinical trials.…”
Section: Innovative Solutions To Boost Effective Innate Responsesmentioning
confidence: 99%